"Passenger gene" problem in transgenic C57BL/6 mice used in hearing research. (September 2020) - Suzuki, Jun; Inada, Hitoshi; Han, Chul; Kim, Mi-Jung; Kimura, Ryuichi; Takata, Yusuke; Honkura, Yohei; Owada, Yuji; Kawase, Tetsuaki; Katori, Yukio; Someya, Shinichi; Osumi, Noriko
Highlights: Fabp7 knockout (KO) mice on a C57BL/6 background had remaining 129/Sv genes. The 129/Sv-derived Cdh23 753GG gene traveled with the target gene. The "passenger gene problem" should be considered in use of transgenic mice. Abstract: Despite recent advances in genome engineering technologies, traditional transgenic mice generated on a mixed genetic background of C57BL/6 and 129/Sv mice remain widely used in age-related hearing loss (AHL) research, since C57BL/6 mice exhibit early onset and progression of AHL due to a mutation in cadherin 23-encoding gene ( Cdh23 753G>A ). In these transgenic mice, backcrossing for more than 10 generations results in replacement of the donor background (129/Sv) with that of the recipient (C57BL/6), so that approximately 99.9% of genes are C57BL/6-derived and are considered congenic. However, the regions flanking the target gene may still be of 129/Sv origin, creating a so-called "passenger gene problem" where the normal 129/Sv-derived Cdh23 753G allele can travel with the target gene. In this study, we investigated the role of fatty acid-binding protein 7 (Fabp7), which is important for cellular uptake and intracellular trafficking of fatty acids in the cochlea, using traditional Fabp7 knockout (KO) mice on the C57BL/6 background. We found that Fabp7 KO mice showed delayed AHL progression and milder cochlear degeneration. However, the genotype of the Cdh23 region flanking Fabp7 was still that of 129/Sv origin ( Cdh23 753GG ). Our findings reveal the potential risk of contamination for traditional transgenic mice generated on the C57BL/6 background.